Chinese guidelines for the diagnosis and treatment of human immunodeficiency virus infection/acquired immunodeficiency syndrome (2024 edition) - Acquired Immunodeficiency Syndrome Professional Group, Society of Infectious Diseases, Chinese Medical Association; Chinese Center for Disease Control and Prevention; Wei Zhao (​​​​​​​​Infectious Diseases & Immunity)
Abstract. The Acquired Immunodeficiency Syndrome Professional Group of the Society of Infectious Diseases of the Chinese Medical Association formulated the first edition of the Chinese Guidelines for the Diagnosis and Treatment of human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) (referred to as the Guidelines) in 2005. The 2024 edition of the Guidelines has been compiled by updating the 2021 fifth edition, incorporating the latest research advancements in antiviral therapy, comprehensive management, opportunistic infections, concurrent tumors, and the prevention and intervention of HIV infection. The new edition also introduces a new section on “Incomplete immune reconstitution”, proposes the concept of “HIV vulnerable populations” for the first time with recommendations for their diagnosis and treatment. This edition of the Guidelines covers 14 sections: epidemiology, pathogenic characteristics, laboratory tests, pathogenesis, clinical presentation and staging, diagnostic criteria, common opportunistic infections, antiretroviral therapy, immune reconstitution inflammatory syndrome, incomplete immune reconstitution, AIDS-related neoplasms, prevention of mother-to-child transmission and conception in serodiscordant couples, pre- and post-exposure prophylaxis, and whole-course management of HIV infection. This edition of the Guidelines aims to assist clinical physicians in making informed decisions in the diagnosis, treatment, and management of HIV/AIDS and will be periodically revised and updated based on domestic and international research progress.